The Influence of Work Ethic, Job Satisfaction, and Organizational Citizenship Behavior (OCB) on Work Productivity of State Elementary School Teachers in Mawar Village, Banjarmasin City - Zakaria Zakaria (PT. Hanken SUkses Jaya, 2021)
This study aims to determine the effect of work ethic, job satisfaction, and OCB on the work productivity of State Elementary School (SDN) teachers in Mawar Village, Banjarmasin City. The method in this study uses quantitative methods, and data collection methods are carried out through questionnaires distributed to the research population, namely all teachers at SDN in Mawar Village, Banjarmasin City, totalling 58 people. Data analysis used the F test and T-test. The results of this study indicate that the work ethic variable partially has a significant effect on teacher work productivity, the job satisfaction variable partially has a substantial impact on teacher work productivity, the organizational citizenship behaviour variable partially has an enormous effect on teacher work productivity: work ethic, job satisfaction. OCB simultaneously have a significant impact on teacher work productivity.